From solitude to solidarity mommune-generative center for single mothers in Quezon City - Pintor, Reuben Cyril B.
Single mothers face multifaceted challenges that are often worsened by societal norms and inadequate support structures. Despite the increasing prevalence of single motherhood in the Philippines, current legislation and support programs fail to address the unique hardships experienced by this vulnerable demographic. Notably, there is a lack in the provision of accommodations and dedicated facilities tailored to the distinctive needs of single mothers in the country. This research aims to bridge the gap by proposing an innovative architectural solution designed to cater to the specific needs of single mothers. A qualitative meta-analysis of relevant literature and interviews with both experts and single mothers were used to gain insights from the challenges and coping strategies employed by single mothers, which were then incorporated into the design approach. The research output is envisioned as a community center guided by the principles of communal child-rearing, coliving, and social enterprise. It features spaces that empower single mothers economically and socially. Overall, this proposal highlights the importance of developing infrastructural support for single mothers, which acknowledge and meet their unique needs.